КОНЦЕПЦИЯ ИСКУССТВА ФЕДОРА ДОСТОЕВСКОГО В КОНТЕКСТЕ ЗАПАДНОЕВРОПЕЙСКОЙ КАТЕГОРИИ ВОЗВЫШЕННОГО - Kropaczewski, Krzysztof (Studia Rossica Posnaniensia, 2008)
The article depicts the problems of functioning of the beauty category in Dostoyevsky’s literary works and journalistic expressions at the background of the changes in sublimity category comprehension happening in Western Europe in the 19th and 20th centuries. Such a perspective allows to treat the esthetics sphere in the author of Besy's legacy as the element of the discussion with the Western European system of values.